Investigations on Plot Size Vis-a-vis Point Sampling a Pilot Study - Joshi, S. C.; Tomar, M. S. (Indian Forester, 1976)
The paper summarises the results of a pilot study carried out in Vidisha Forest Division for studying relative efficiency of three fixed-size plota vis-a-vis point sampling with wedge prism of BAF 1. Measurements were recorded on 37 sample locations on a set of 3 fixed-size plots (square) of 0.05, O.10 and 0.125 ha along with basal area tally. Aerial photographs were used preliminary stratification and plots were confined to wood forest. In terms of cost effectiveness, amongst the three fixed plots tested, the smallest sampling unit of 0.05 ha was 1.51 and 1.68 times more efficient than O.10 and 0.125 ha plots respectively with respect to gross volume. Point sampling, however, proved to be 1.64, 2.56 and 1.07 time. More efficient over fixed plot of 0.05 ha in relation to gross volume, teak volume and total number of stems/ha respectively. Basal area tally and volume showed a strong linear relationships which can be directly applied for volume estimation even for small areas such as coupes, compartments, felling series, etc, thereby resulting in considerable saving of cost and time, particularly in working plan surveys.